2003
DOI: 10.1177/107424840300800206
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of Nebivolol plus Pravastatin is Associated with a More Beneficial Metabolic Profile Compared to that of Atenolol plus Pravastatin in Hypertensive Patients with Dyslipidemia: A Pilot Study

Abstract: Nebivolol, a selective beta1-lipophilic blocker, achieves blood pressure control by modulating nitric oxide release in addition to b-blockade. This dual mechanism of action could result in minimum interference with lipid metabolism compared to atenolol, a classic beta1-selective blocker. Hypertensive patients commonly exhibit lipid abnormalities and frequently require statins in combination with the anti-hypertensive therapy. We conducted this trial in order to clarify the effect on the metabolic profile of be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
1
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 49 publications
3
42
1
4
Order By: Relevance
“…The nitric oxide-mediated vasodilatory activity differs this drug from other beta blockers, hence this action can result in interference with lipid metabolism (36). The hypertension exhibits hyperlipidemia, therefore hypertensive therapy requires lipid lowering therapy in patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nitric oxide-mediated vasodilatory activity differs this drug from other beta blockers, hence this action can result in interference with lipid metabolism (36). The hypertension exhibits hyperlipidemia, therefore hypertensive therapy requires lipid lowering therapy in patients.…”
Section: Discussionmentioning
confidence: 99%
“…The hypertension exhibits hyperlipidemia, therefore hypertensive therapy requires lipid lowering therapy in patients. In a study (36), nebivolol was compared with atenolol, and authors considered nebivolol to be more advantageous with its lipid lowering and antiinflammatory effects in addition to its antihypertensive effects. In an experimental study, nebivolol was shown to prevent oxidative stress in rats with ischemia-induced cerebral injury (37).…”
Section: Discussionmentioning
confidence: 99%
“…It was significantly decreased glucose clearance value in the atenolol group. In 30 patients suffering from hypertension and insulinfree diabetes, for 24 weeks nither nebivolol (5 mg), nor atenolol (50 mg) did not affect the utilization of glucose and insulin sensitivity [10,14,15,20].…”
Section: Discussionmentioning
confidence: 94%
“…Высокая клиническая эффективность небиво-лола при различных сердечно-сосудистых заболе-ваниях -АГ, ИБС, в том числе у больных с СД на сегодняшний день имеет большую доказатель-ную базу -более 70 исследований [30][31][32][33][34][35].…”
Section: российский кардиологический журнал № 4 (102) | 2013unclassified